Growth and yield performance of sunflower (Helianthus annuus L.) as influenced by cow dung and NPK fertilizers (Dhaka University Journal of Biological Sciences, 2023)
A field experiment was conducted at the research farm of Charfasson Govt. College, Bhola, Bangladesh in rabi season in 2015-2016 to evaluate the effect of cow dung and chemical fertilizers on growth and yield of sunflower cv. BARI-2 (Keroni-2). Highest plant height (208.4 cm), leaf area (410.5 cm2) and leaf area index (12.75) were recorded in T16 (7.5 ton CD ha-1 +N120P90K150kg ha-1). Highest dry matter yield viz. stem (60.67g plant-1) found in treatment T16 (7.5 ton CD ha- 1+N120 P90K150kg ha-1). Maximum dry weight of leaf (25.33g plant-1) and dry weight of root (12.83g plant-1) were found in treatment T15 (7.5 ton CD ha-1 +N80P60K100kg ha-1). Highest dry weight of seed (64.7 g plant-1) and dry wt. of 100 seed (9.8 g) were found in treatment T15 (7.5 ton CD ha-1 +N80P60K100kg ha-1) but the highest number of seed (735.7plant-1) and florescence diameter (52.67 cm) were observed in treatment T13 (5 ton CD ha-1 +N120P90K150kg ha-1). Maximum total dry matter yield per plant was 92.01 g and per hectare was 5.75 ton in T16 (7.5 ton CD ha-1+N120P90K150kg ha-1). Results revealed that the combined application of cow dung and NPK fertilizers produced better growth and yield of sunflower in field condition at the coastal belt of Bangladesh.Dhaka Univ. J. Biol. Sci. 32(1): 83-90, 2023 (January)